Disjunct distribution of Uzelothripidae (Thysanoptera) new to Australia - Tree, Desley J (Zootaxa, 2009)
The order Thysanoptera (thrips) is divided into two sub-orders, Terebrantia with eight families, and Tubulifera with just one family. Within Terebrantia, the family Uzelothripidae contains only a single genus and species, Uzelothrips scabrosus Hood. This is believed to have derived independently from an early offshoot of the thysanopteran sub-order Terebrantia (Mound & Marullo, 1996), and has no close phylogenetic relationship with any other thrips taxa (Mound & Morris 2007). The form of the wings, antennae, cephalic tentorium and female ovipositor are unlike those of any other Thysanoptera (Fig. 1). The forewings (when present) have no longitudinal veins, but have marginal cilia arising from sockets. The antennae are exceptionally long and slender, and the third segment has a unique circular sensorium ventrally near the apex. The cephalic tentorium is well developed, and the ovipositor is membranous and protusible with no developed valves (Mound et al. 1980, Moritz et al. 2001).